STUDENTS’ PERCEPTION TOWARDS GOOGLE CLASSROOM AS E-LEARNING TOOL (A Case Study of Master of English Education of the Second Semester at STKIP PGRI Sidoarjo) - J. Priyanto Widodo; Joko Slamet (Widya Mandala Surabaya Catholic University, 2020)
E-Learning is a moderately new phenomenon where currently the educators and students are grappling with the idea of its implementation and adaptation. E-learning has contributed to the learning process can be done not only in the classroom but any places and every time, especially within the COVID-19 issue. Google Classroom is one of the tools implemented among e-learning scan be applied. The purpose of this research is to identify the students’ perception of the implementation Google Classroom as a learning tool for students of Master of English Education at STKIP PGRI Sidoarjo. Descriptive quantitative method was applied in conducting the research. Questionnaire which was distributed to the 19 students was the instrument of this research. The results showed google classroom as a tool of e-learning is a useful application can be applied during e-learning within the issue of Covid-19 to the second semester students of Master of English Education (MPBI Batch 5) at STKIP PGRI Sidoarjo in regard it is a solution of e-learning in case it is useful, effective and also helps students in assisting in the e-learning.